A Generalized Strategy for the Synthesis of Large‐Size Ultrathin Two‐Dimensional Metal Oxide Nanosheets. Issue 30 (19th June 2017) - Zhao, Hewei; Zhu, Yujie; Li, Fengshi; Hao, Rui; Wang, Shaoxiong; Guo, Lin
Abstract: Two‐dimensional (2D) nanomaterials show unique electrical, mechanical, and catalytic performance owing to their ultrahigh surface‐to‐volume ratio and quantum confinement effects. However, ways to simply synthesize 2D metal oxide nanosheets through a general and facile method is still a big challenge. Herein, we report a generalized and facile strategy to synthesize large‐size ultrathin 2D metal oxide nanosheets by using graphene oxide (GO) as a template in a wet‐chemical system. Notably, the novel strategy mainly relies on accurately controlling the balance between heterogeneous growth and nucleation of metal oxides on the surface of GO, which is independent on the individual character of the metal elements. Therefore, ultrathin nanosheets of various metal oxides, including those from both main‐group and transition elements, can be synthesized with large size. The ultrathin 2D metal oxide nanosheets also show controllable thickness and unique surface chemical state. Abstract : A generalized and facile strategy is used to synthesize large‐size ultrathin 2D metal oxide nanosheets by using graphene oxide (GO) as a template in a wet‐chemical system. The nanosheets fabricated following the strategy show controllable thickness and a unique surface chemical state.